IMPLIKASI ASEAN ECONOMIC COMMUNITY BLUEPRINT TERHADAP PERKEMBANGAN PERDAGANGAN INDONESIA KE SINGAPURA - Yufani, Elsa; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research explains about the effect of free flow of goods as a form of schedule blueprint strategies for the scheme towards the ASEAN Economic Community (AEC) on the development of Indonesia's trade to Siangapura. ASEAN Economic Community (AEC) 2015 will open up more opportunities for free flow of goods, services, investment, capital to labor through out the ASEAN region. On one hand, implementation of free flow of goods ASEAN Economic Community (AEC) would provide opportunities for expanding and intensifying Indonesia. The efforts to expand and intensify export to ASEAN market would give optimum result if it is accompanied by promoting cooperation among industries in ASEAN through regional production network. On the other hand, free flow of goods ASEAN Economic Community (AEC) would also become a threat for Indonesia and domestic market if businessmen as well as government have not prepared yet for this new era competition in ASEAN. Since ASEAN member countries produce almost similar products, the challenge for businessmen is to produce competitive products based on differentiation, efficiency and innovation.This research uses the perspective of liberalism that supports the international economy based on free trade, because it involves the cooperation in the field of trade between Indonesia and Singapore. The data sources used in this research are books, journals, working papers, and valid news from websites.Implementation of the ASEAN Economic Community Blueprint will have implications on the economy of Indonesia and ASEAN in terms of macro-economic conditions or competition between the regions visible from local revenues, state investment allocation and composition of international trade.Keywords: Blueprint, Economic Integration, Cooperation, Trade.